Evaluation of topical bioassay method of imidacloprid and thiamethoxam insecticides on stingless bee (Trigona itama) - Zulkiffly, Nur Aida (2018)
Stingless bees (Trigona itama) are restricted to the tropical regions of the world and are considered as important pollinators of various wild and cultivated plants. Commercially important plants such as coconut, carambola, mango, strawberry, rambutan and others were confirmed pollinated by stingless bees. Unfortunately, nowadays most farmers rely too much on insecticide to protect the crops. Researchers have found that insecticides are dangerous to bees and may kill them. Many insecticides toxicity studies are commonly conducted on honey bees and very lack study on the stingless bees. As the size of the stingless bees (Trigona itama) is smaller than honey bees, therefore it would be more sensitive to the insecticides. The main purpose of this study is to determine the toxicity level of neonicotinoid insecticides, which are Thiamethoxam and Imidacloprid on stingless bees. This study was conducted by using topical bioassay method on Trigona itama to determine the LD50 (in ppm value) of the insecticides. Four different concentrations for each insecticides and a control were prepared for four replications. Every replication requires ten individual foragers of Trigona itama. The mortality number of Trigona itama were recorded at 24 hours and 48 hours after treatment. The results showed that stingless bees were highly susceptible to Imidacloprid (LD50=0.225 ppm, 24 HAT and 0.122 ppm, 48 HAT) compared to Thiamethoxam (LD50=2.009 ppm, 24 HAT and 1.057 ppm, 48 HAT). Comparison of LD50 values for both insecticides between Apis mellifera sp. and Trigona itama showed that Trigona itama is more easily harmed than Apis mellifera sp.